2006
DOI: 10.2147/copd.2006.1.4.425
|View full text |Cite
|
Sign up to set email alerts
|

Role of N-acetylcysteine in the management of COPD

Abstract: The importance of the underlying local and systemic oxidative stress and inflammation in chronic obstructive pulmonary disease (COPD) has long been established. In view of the lack of therapy that might inhibit the progress of the disease, there is an urgent need for a successful therapeutic approach that, through affecting the pathological processes, will influence the subsequent issues in COPD management such as lung function, airway clearance, dyspnoea, exacerbation, and quality of life. N-acetylcysteine (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 98 publications
(120 reference statements)
0
78
0
5
Order By: Relevance
“…30 Although the clinical use of GSH and GSH precursors is rather limited to the use of N-acetylcysteine in acetaminophen toxicity, as a mucolytic in respiratory disease, and experimentally in the prevention of contrast-induced nephropathy, this study has important clinical implications for consumers and for providers in nonallopathic disciplines, such as complementary and alternative medicine, in which oral nutritional supplementation is commonplace. [31][32][33][34][35] The results of this study determined that short-term, oral intake of GSH does not improve glutathione status, nor reduce markers of oxidative stress in healthy adults, and thus routine supplementation may not offer health benefits in the absence of disease or oxidative challenge.…”
Section: Figmentioning
confidence: 85%
“…30 Although the clinical use of GSH and GSH precursors is rather limited to the use of N-acetylcysteine in acetaminophen toxicity, as a mucolytic in respiratory disease, and experimentally in the prevention of contrast-induced nephropathy, this study has important clinical implications for consumers and for providers in nonallopathic disciplines, such as complementary and alternative medicine, in which oral nutritional supplementation is commonplace. [31][32][33][34][35] The results of this study determined that short-term, oral intake of GSH does not improve glutathione status, nor reduce markers of oxidative stress in healthy adults, and thus routine supplementation may not offer health benefits in the absence of disease or oxidative challenge.…”
Section: Figmentioning
confidence: 85%
“…Some systematic reviews and meta-analyses have suggested that NAC prevents exacerbations and improves symptoms in Chronic obstructive pulmonary disease (COPD) patients [94][95][96][97][98] (Table 2), however, probably with little or no effect on the lung function parameters [96].…”
Section: N-acetylcysteinementioning
confidence: 99%
“…1,2 Mucus hypersecretion is associated with declines in pulmonary function and quality of life, excess cough, discomfort, and exacerbation of conditions such as COPD. 3,4 Mucoactive agents may increase sputum expectoration or decrease hypersecretion of mucus. 1,5,6 Mucolytic agents such as N-acetylcysteine alter disulfide bonds that comprise mucus proteins and may decrease mucus viscosity.…”
Section: Introductionmentioning
confidence: 99%